The Christmas book of legends & stories - Smith, Elva Sophronia, 1871-1965; Hazeltine, Alice Isabel, 1878-1959 (Lothrop, Lee & Shepard Company, 1944)
An anthology of poems, stories, and plays which reflect the religious aspects of Christmas.